Criminal Imposition on Perpetrators of Joint Violence Resulting in Death from the Perspective of Islamic Jurisprudence - Nafis Dwi Rizky; Ali Maskur; Mohamad Solek (Journal of Law, Politic and Humanities, 2026)
Collective violence resulting in death remains a serious criminal offense, often arising from acts of vigilantism (eigenrichting). Such conduct violates both positive criminal law and the Islamic legal principle of protecting human life. This study analyzes the judicial considerations in Decision Number 681/Pid.B/2024/PN Smg and examines the offense from the perspective of fiqh jinayah. Using a normative legal method with case and conceptual approaches, the research relies on the Indonesian Criminal Code, court decisions, the Qur’an, and relevant legal literature. The findings show that the court imposed criminal sanctions under Article 170 paragraph (2) point 3 of the Criminal Code after determining that all legal elements of the offense had been proven through witness testimonies, defendants’ statements, documentary evidence, and visum et repertum. From the perspective of fiqh jinayah, the defendants’ actions are classified as qatl syibh al-‘amd (quasi-intentional homicide) because the violence was intentional but not aimed directly at causing death. The collective nature of the offense also reflects the concept of isytirak fi al-jarimah, which attributes criminal responsibility to all participants involved in the resulting death.